PENGARUH EFEKTIVITAS PENGELOLAAN ASET, KEBIJAKAN PEMBIAYAAN DAN PENGELOLAAN PRODUKSI TERHADAP PROFITABILITAS DENGAN LIKUIDITAS SEBAGAI PEMODERASI (Studi Empiris Pada Perusahaan Pengelola Bandara Udara Di Asia Pasifik Periode 2010 – 2020) - Yogi Prastyo Suwandi; Edyanus Herman Halim; Alfiati Silfi (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
This study aims to examine and investigate the factors that influence the profitability of airport management companies in Asia Pacific. In this study, the Dependent Variable (Y) is Company Profitability, Independent Variable 1 (X1) is Investment Policy, Independent Variable 2 (X2) is Financing Policy and Independent Variable 3 (X3) is Production Management and Liquidity as Moderating Variable. In addition, it will be studied how the financial management behavior of airport management industrial companies in Asia Pacific especially at this time of the Covid 19 Pandemic. In sampling using criteria, namely an airport management company that serves passengers over 30,000,000 Pax/year, a management company Airports that serve Domestic and International flights, Issue Annual Reports regularly in the 2010 – 2020 period in a row. There are 6 Airport Management Companies in Asia Pacific that meet these criteria. The results of this study indicate that the Investment Policy, Financing Policy and Production Management affect the Company's Profitability. Meanwhile, liquidity cannot moderate the effect of Investment Policy, Financing Policy and Production Management on profitability.